If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3(0) = -81 Multiply -3 * 0 9x + 0 = -81 Anything times zero is zero. 9x + 0 = -81 Reorder the terms: 0 + 9x = -81 Remove the zero: 9x = -81 Solving 9x = -81 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '9'. x = -9 Simplifying x = -9
| 8w^2+2w-1=0 | | 2+2p=6 | | 168/x=12 | | 9x-3y=-81 | | 3h^2+10h-8=0 | | n-15=31 | | 104=2v^2+8 | | x+5=4x-13 | | 12=2L+(10) | | 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 |